Sustainability Digital Learning in Civic Education: An Effort to Improve Student’s Civic Skills - Sopianingsih, Pitria; Insani, Nisrina Nurul; Anggraini, Diana Noor; Malika, Aura Sabrina (CV. Rayyan Dwi Bharata, 2025)
Today, the behavior of the younger generation is characterized by a tendency to ignore problems that make a lack of critical thinking, problem solving, and lack of relevant digital skills such as media literacy, critical evaluation of information and productive use of technology which causes a lack of student skills in adapting. This problem of behavioral and character degradation is a challenge for Civics learning. Civics learning needs a new nuance to emphasize limited material but there needs to be material and learning that is sustainable throughout life. So, there needs to be civic skill development through digital learning with a touch of SDGs values. This research aims to develop sustainable digital learning with perceived outcomes can improve students' Civic Skills... The research approach used is a quantitative approach with a correlational method with a sample of FTV students who contract Civic Education courses at the Indonesian Education University. Data collection techniques with questionnaires, observation, and documentation. The results showed that the Sustainability Digital Learning Model in Civics Learning can improve civic skills, such as intellectual skills and participation skills.